TRANSPARENT BACTERIAL CELLULOSE NANOCOMPOSITE HYDROGELS - LI, XINSHENG; WAN, WAN-KEI; PANCHAL, CHANDRAKANT J (2011)
A transparent polymeric nanocomposite hydrogel is provided, wherein the polymeric nanocomposite hydrogel is made from a water insoluble polymer, i.e. poly(2-hydroxyethyl methacrylate) (PHEMA) or/and crosslinked PHEMA and a water insoluble nanofiber, i.e., bacterial cellulose (BC). Disclosed is a synthetic route for polymeric nanocomposites hydrogels. The preferred polymeric nanocompositions are produced through free radical polymerization of HEMA monomer in the presence of bacterial cellulose with an assistance of ultrasound to enhance the mixing of bacterial cellulose, initiator, and the monomers. The polymeric nanocomposite hydrogel is then formed by immersion of the dry polymeric nanocomposite in water. Disclosed is a high transmittance polymer nanocomposite hydrogel with a preferred BC loading less than 0.1%, water content of about 40% in weight, good mechanical integrity and strength. The disclosed polymer nanocomposite hydrogel and compositions pertain to hydrogel applications, particularly contact lenses and optic components for biosensor.